Effect of chemical–thermal activation on the properties of recycled fine powder cementitious materials - Liuyi Chen; Muwang Wei; Nengzhong Lei; Huawei Li (Case Studies in Construction Materials, 2024)
Recycled fine powder (RFP) collected from construction and demolition waste resources is difficult to use in large quantities due to its low activity. To promote the activity of RFP and maximize its economic and environmental benefits, it is necessary to develop an appropriate activation method for active activation. Therefore, in this study, chemical, thermal, and combined chemical–thermal activation were employed to stimulate the activity of RFP. Furthermore, the related activation mechanisms were analyzed through compressive strength tests of mortar and concrete, X-ray diffraction, thermogravimetric analysis, scanning electron microscopy and other methods. Results indicate that, at a substitution rate of 30%, chemical activation has a minimal impact on the strength of the RFP mortar system, with an activity index reaching 68.3%. Comparatively, thermally activated systems at 700 °C exhibit higher strength than chemically activated systems, with the activity index reaching 77.4%. The efficacy of the three methods in enhancing the RFP–cement cementitious system at varying substitution rates follows this order: thermal activation > chemical–thermal activation > chemical activation. Microscopic analysis reveals that chemical activation minimally influences the hydration development of the systems. In contrast, thermal activation substantially promotes the hydration degree (α). α values for the three activation methods are as follows: thermal activation (38.72%) > chemical–thermal activation (37.83%) > chemical activation (32.85%). Thermal activation triggers the generation of more cementitious materials, enhances structural compactness, and facilitates the interface bonding of the concrete–aggregate interface transition zone at substitution rates of 45% and 60%. This study is a valuable reference for identifying suitable methods for activating RFP and promoting its substantial production.